The characteristic of agarose extraction from dimethyl sulfide and isopropanol (Research, Society and Development, 2020)
Introduction. This study aimed to obtain agarose product with market standard quality which could be applied for electrophoresis. Methods. The material used in agarose extraction process was dried agar – agar bar extracted using dimethyl sulfide and soaked in isopropanol solution with 85%, 90%, and 95% of isopropanol concentration. The parameter which observed in this study was consisted of yield, water content, sulfate content, ash content, gel strength and electrophoresis gel. Results. The average score of agarose yield using different concentrations of isopropanol (IPA) was around 46.76% - 57.53% with the lowest yield of 46.76% and the highest yield of 57.53%. Meanwhile the average water content ranged from 18.32% to 18.64%. The average ash content was around 0.15% - 0.16% and the average sulfate content was 0.14% - 0.15%. The average strength of a 1% gel prepared in isopropanol was 1170 – 1183.33 gr/cm2. Best IPA concentration to soak agarose extract was on 95% concentration, with market standard characteristic as 57.54% of yield, 18.35% of water content, 0.14% of sulfate content, 0.15% of ash content and 1183.33 of gel strength. Conclusions.The application of electrophoresis of agarose gel showed that the bands of large molecular DNA fragment could not separate. Partially hydrolyzed protein samples had higher protein content, lighter color, and lower degree of denaturation and better functional properties compared to the traditional protein isolates.